A giant pyogenic granuloma on the hard palate - Santosh Kumar Swain (Apollo Medicine)
Pyogenic granuloma (PG) is a hyperplastic and inflammatory lesion found in the oral cavity. Exuberant tissue response to trauma or local irritation is believed to cause PG. In the second decades of their life, it is commonly seen in young women, owing to vascular hyperplasia caused by female hormones. The clinical presentations are smooth or lobulated exophytic mass and sessile or pedunculated red to pink. The size of the PG may vary from a few millimeters to several centimeters. Gingiva is the common site for PG in the oral cavity. PG very rarely involves the hard palate. However, there is a high chance of PG in the oral cavity during pregnancy. Therefore, complete surgical excision of the lesion is the treatment of choice. Here, this case report presents PG in the hard palate region of an 18-year-old female, a scarce location for this lesion.